In the country of the blind [large type] - Hoagland, Edward (Center Point Large Print, 2017)
"Press, a stockbroker going blind, has lost his job and his wife and is holed up in his Vermont cabin surrounded by a hippy commune, drug runners, farmers-gone-bust, blood-thirsty auctioneers, and general ne'er-do-wells. Solace and purpose come from the unlikeliest sources as he learns to navigate his new landscape without sight"--